Labour market inequality in two Asian giants: Indonesia and India compared - Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
We examine the nature of labour market inequality in Indonesia and India, using a common conceptual approach drawing from the job ladder framework. In the framework, we differentiate between self-employment and wage-informal and between formal, upper tier informal, and lower tier informal jobs. We find that both countries have a large proportion of workers in lower tier jobs, though the importance of wage-employment is larger in Indonesia. There are more workers in formal wage-employment in Indonesia than India. There are also sharp disparities in the earnings of workers in different tiers of the labour market in Indonesia and India, and there is limited evidence of convergence of the earnings of the lower tier informal workers to that of formal workers, at least for Indonesia. We also find that gender and educational level are important correlates of work status in both countries. Females and less educated workers occupy the lower tiers of the labour markets in the two countries.
Keywords: J21; O17; P50; 330; job ladder; labour market inequality; informality; Indonesia; India